2008
DOI: 10.1016/j.yjmcc.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mechanisms of pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH)1 is a complex disease that causes significant morbidity and mortality and is clinically characterized by an increase in pulmonary vascular resistance. The histopathology is marked by vascular proliferation/fibrosis, remodeling, and vessel obstruction. Development of PAH involves the complex interaction of multiple vascular effectors at all anatomic levels of the arterial wall. Subsequent vasoconstriction, thrombosis, and inflammation ensue, leading to vessel wall remodelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
179
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(191 citation statements)
references
References 236 publications
3
179
0
7
Order By: Relevance
“…Sildenafil decreases the activity of myosin light chain kinase and reduces the speed of myosin phosphorylation, so that the smooth muscle cell is contractility reduced, and pulmonary vascular smooth muscle can dilate (Ignarro, 1990). Secondly, sildenafil reduces pulmonary arterial pressure, decreasing the shearing forces on endothelial cells and the mRNA expression of vascular endothelial growth factor (VEGF) (Chan and Loscalzo, 2008;Rondelet et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil decreases the activity of myosin light chain kinase and reduces the speed of myosin phosphorylation, so that the smooth muscle cell is contractility reduced, and pulmonary vascular smooth muscle can dilate (Ignarro, 1990). Secondly, sildenafil reduces pulmonary arterial pressure, decreasing the shearing forces on endothelial cells and the mRNA expression of vascular endothelial growth factor (VEGF) (Chan and Loscalzo, 2008;Rondelet et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Both might contribute to vascular remodeling in end-stage disease in PAH patients. [3][4][5] In hypoxia, Egr-1 has been shown to be up-regulated in lungs 22,23 and isolated fibroblasts 24 subjected to chronic hypoxia. Focusing on the pulmonary vessels, Yan and colleagues 22 have shown that in lungs of mice subjected to hypoxia, Egr-1 is specifically produced in pulmonary vessel smooth muscle cell.…”
Section: Egr-1 Transcription During Pulmonary Vascular Remodelingmentioning
confidence: 99%
“…NAB2 may have its Egr-1 in PAH Development 2207 AJP November 2011, Vol. 179,No. 5 direct effect on preventing a permanent transcription of Egr-1, as seen at early-stage PAH (MϩF 14).…”
Section: Egr-1 Transcription During Pulmonary Vascular Remodelingmentioning
confidence: 99%
See 2 more Smart Citations